A flexible peptide linking the periplasmic and cytoplasmic domains of MxiG controls type III secretion signaling and stable sorting platform assembly in Shigella - Tachiyama, Shoichi; Muthuramalingam, Meena; Whittier, Sean K.; Chang, Yunjie; Yue, Jian; Younis, Waleed; Picking, Wendy L.; Liu, Jun; Picking, William D. (Frontiers in Cellular and Infection Microbiology, 2025)
Shigella flexneri uses its type III secretion system (T3SS) to invade human enterocytes. The T3SS injectisome is controlled by proteins at the tip of an exposed needle that sense host cell contact. Substrate selection and powering of secretion is controlled by a cytoplasmic assembly called the sorting platform (SP). The Shigella SP possesses six pod structures linked to a central ATPase via radial spokes. The SP associates with the injectisome inner membrane ring (IR) via the adaptor protein MxiK. The major IR component is MxiG, whose globular periplasmic domain (MxiGP) packs with MxiJ in a 24-fold symmetry. MxiG also has a transmembrane helix attached to a small cytoplasmic domain (MxiGC) via a flexible linker peptide. Change from the IR’s 24-fold symmetry to six-fold symmetry for the SP in Shigella occurs via MxiGC pairs that associate with MxiK. The intervening pairs shift to the center of the IR/SP assembly, which is distinct from what is seen for Salmonella. This implicates the linker in dynamic motions at the IR-SP interface, but the functional importance of the linker is unknown. Using a library of mutants, we found that the linker can accept diverse mutations without eliminating injectisome function. However, some mutants were found to give rise to subpopulations able to form needles and secrete effectors in the absence of a stably assembled SP. Mutants lacking the entire linker could not secrete any effector proteins (e.g. the IpaD tip protein) and had no T3SS-related virulence functions, however, there were subpopulations that could still secrete MxiH and assemble visible needles. In contrast, a very short linker could export IpaD to the needle tip, but could not rapidly respond to external secretion signals and were thus unable to quickly enter epithelial cells. These findings implicate the MxiG linker in signaling processes that are sensed at the needle tip. Our findings suggest that the native MxiG linker peptide has evolved to maximize T3SS function at steps beyond needle formation, while needle formation can occur even when the SP is highly destabilized.